2011
DOI: 10.1088/1475-7516/2011/10/033
|View full text |Cite
|
Sign up to set email alerts
|

Low-scale supersymmetry from inflation

Abstract: We investigate an inflation model with the inflaton being identified with a Higgs boson responsible for the breaking of U(1) B−L symmetry. We show that supersymmetry must remain a good symmetry at scales one order of magnitude below the inflation scale, in order for the inflation model to solve the horizon and flatness problems, as well as to account for the observed density perturbation. The upper bound on the soft supersymmetry breaking mass lies between 1 TeV and 10 3 TeV. Interestingly, our finding opens u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
40
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 72 publications
1
40
0
Order By: Relevance
“…Instead, let us focus on a new inflation model recently proposed by the present authors [2], in which the B−L Higgs boson plays the role of the inflaton. The theoretical framework is the minimal extension of the standard model (SM), namely, SM + right-handed neutrinos + gauged U(1) B−L .…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Instead, let us focus on a new inflation model recently proposed by the present authors [2], in which the B−L Higgs boson plays the role of the inflaton. The theoretical framework is the minimal extension of the standard model (SM), namely, SM + right-handed neutrinos + gauged U(1) B−L .…”
mentioning
confidence: 99%
“…In Ref. [2] it has been shown that the inflation model using the B−L Higgs boson works successfully if there is supersymmetry (SUSY) at a scale below ∼ 10 3 TeV = PeV. The presence of SUSY below the PeV scale is crucial for canceling the Coleman-Weinberg (CW) potential [5] arising from the B−L gauge boson loop.…”
mentioning
confidence: 99%
See 3 more Smart Citations